The College of Education, University of the Philippines a descriptive study - Chaiyaprasithi, Malee 1939-
The College of Education at the University of the Philippines, located at Diliman, Quezon City was described in this study. Specifically, it attempted to describe the College of Education in terms of: 1) its manifest aims and objectives, 2) the nature of its organizational structure, the duties and functions of the members of its administrative personnel, 3) its faculty and their qualifications, 4) the requirements on admissions and graduation of both Filipino and foreign students and the nature of the curricular offerings in both the graduate and undergraduate levels, and 5) the scholarships and study grants available to its students and to those desiring to enroll in any of its programs and information as to the external agencies instrumental in its development.